METHODOLOGY OF DEVELOPING ACMEOLOGICAL ACCOMPLISHMENT IN FUTURE TEACHERS - Tuychieva Sabina Sherzodovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article examines the methodology of developing acmeological accomplishment in future teachers. The research highlights the importance of professional competence, reflective thinking, and innovative pedagogical activity. Special attention is given to the formation of creative individuality and the achievement of the highest levels of professional development. The acmeological approach is analyzed as a key factor in ensuring the effectiveness of pedagogical activity and continuous self-improvement.